Prevalence and Correlates of Social Stigma Toward Diabetes: Results From a Nationwide- Survey in Singapore - Subramaniam, Mythily; Abdin, Edimansyah; Bhuvaneswari, S.; AshaRani, P. V.; Devi, Fiona; Roystonn, Kumarasan; Wang, Peizhi; Samari, Ellaisha; Shafie, Saleha; Vaingankar, Janhavi Ajit; van Dam, Rob M.; Lee, Eng Sing; et al. (Frontiers in Psychology, 2021)
Aims: To examine the extent of social stigma towards diabetes among Singapore’s multi-ethnic general population and determine whether this differs across socio-demographic sub-groups. Methods: Data for this study came from a nationwide cross-sectional study. A diabetes stigma questionnaire comprising Social Distance Scale and Negative Attitudes and Stereotyping Scale was administered to those respondents who had not been diagnosed with diabetes. Exploratory factor analysis was conducted to determine the dimensionality of the instruments and validated using confirmatory factor analysis. Multiple linear regression analysis was conducted to examine associations between socio-demographic factors and measures of diabetes stigma. Results: In all, 2895 participants were recruited from the general population giving a response rate of 66.2%. Factor analyses found that a one-factor model resulted in an acceptable fit for both stigma scales, which measured social distance and negative attitudes and stereotyping respectively. Multiple linear regression analyses identified Indian ethnicity (versus Chinese), higher personal income ((≥SGD2000 versus < SGD 2000) and having close friends or family members who had been diagnosed with diabetes were significantly associated with lower social distance scores while those aged 50-64 years and those with secondary and vocational education (versus degree and above) were significantly associated with higher social distance scores. Those with a personal income of SG2,000 to 3,999 and SGD 6,000 and above, and those with close friends or family members diagnosed with diabetes were significantly associated with lower negative attitudes and stereotyping scores. In contrast those aged 35 years and above, those with primary education and below, and those of Malay ethnicity were significantly associated with higher negative attitudes and stereotyping scores. Conclusions: The study found a relatively low level of stigma towards diabetes in the general population of Singapore, although some stigmatizing beliefs emerged. While greater knowledge of diabetes could reduce stigma, anti-stigma messaging should be incorporated into the ‘War on Diabetes’ programme in Singapore.